2015
DOI: 10.1162/jocn_a_00736
|View full text |Cite
|
Sign up to set email alerts
|

Complementary Roles of Human Hippocampal Subfields in Differentiation and Integration of Spatial Context

Abstract: The unique circuitry of the hippocampus is thought to support the encoding and retrieval of context-rich episodic memories. Given the neuroanatomical differences between the hippocampal subfields, determining their functional roles during representation of contextual features in humans is an important yet unaddressed research goal. Prior studies suggest that during the acquisition of information from the environment, the dentate gyrus (DG) and CA3 subfields rapidly differentiate competing contextual representa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
89
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(99 citation statements)
references
References 73 publications
9
89
1
Order By: Relevance
“…Although it is infeasible to register place cell activity in humans using fMRI, given that the distribution of place cells in rodent hippocampus is nontopographic with respect to the spatial distribution of their firing fields [37], the aforementioned rodent place cell pattern shows striking similarities with our data. Our data are consistent with the absence of sigmoidal neural response patterns in the human hippocampus when participants view highly similar visual scenes [38,39] and a linear scaling of hippocampal responses with changes in the configuration of landmarks in four virtual environments [40]. The attractor-like behavior of place cells also accords with observations in rodents that repeated exposure to less-distinct environments is accompanied by a slower, gradual development of distinct place cell representations [41].…”
Section: Discussionsupporting
confidence: 89%
“…Although it is infeasible to register place cell activity in humans using fMRI, given that the distribution of place cells in rodent hippocampus is nontopographic with respect to the spatial distribution of their firing fields [37], the aforementioned rodent place cell pattern shows striking similarities with our data. Our data are consistent with the absence of sigmoidal neural response patterns in the human hippocampus when participants view highly similar visual scenes [38,39] and a linear scaling of hippocampal responses with changes in the configuration of landmarks in four virtual environments [40]. The attractor-like behavior of place cells also accords with observations in rodents that repeated exposure to less-distinct environments is accompanied by a slower, gradual development of distinct place cell representations [41].…”
Section: Discussionsupporting
confidence: 89%
“…This unified account of spatial context, temporal context and spatiotemporal context aligns well with recent fMRI studies virtual reality suggesting not only that similar regions participate in recovery of spatial and temporal context [66, 67, 64] (see also Fig. 2B).…”
Section: Advances In the Theory Of Temporal And Spatial Contextsupporting
confidence: 88%
“…Overall, convergent data have suggested that CA3 is capable of exhibiting pattern completion or pattern separation, depending on the magnitude of the change in sensory input. The CA1 subfield generally appears to respond linearly to incremental changes in sensory input; however, under some conditions it may respond with an abrupt nonlinear change, perhaps reflecting a switch in its dominant input from the entorhinal cortex to CA3 1820 (but see Stokes et al 21 ). This could be a result of explicit task influences or the requirement for a mnemonic judgment instead of free exploration 19,22 .…”
Section: Empirical Evidence For Pattern Separation In the Hippocampusmentioning
confidence: 99%